Power system frequency control enhancement by optimization of wind energy control system - Mohammad H. Soliman (Elsevier, 2021)
Future trends are increasingly directed towards replacing traditional energy sources by new and renewable energy ones, with Wind Energy coming first in the row of these sources worldwide. The Egyptian electric power system still has a relatively low penetration level, around 3%, of Wind Energy to its generation mix. However, it is planned to increase this ratio to 14.6% by the year 2035. This paper studies the frequency dynamics associated with significant penetration levels of Wind Energy into the Egyptian grid, which leads to reducing the overall system inertia. The control strategy adopted depends on maximizing the wind energy contribution to frequency control, in order to compensate that reduction of system inertia. The Real data of the Egyptian power system model used is verified by the National Electricity Control Centre, updated to the latest values declared and tested under the lowest and highest loads recorded. A modified control loop is added to the control system in order to allow the Wind Energy Conversion System to significantly contribute to the Load Frequency Control. The PI controller gains used in that loop are tuned using three methods; Local Unimodal Sampling, Harmony Search Algorithm and Equilibrium Optimizer (EO). The Equilibrium Optimizer (EO) proved its superiority to the other methods, as it gave the best dynamic response. The simulated results are presented using MATLAB/SMULINK.